Fimasartan for independent reduction of blood pressure variability in mild-to-moderate hypertension - Shin MS; Kang DR; Kim C; Cho EJ; Sung KC; Kang SM; Kim DS; Joo SJ; Lee SH; Hwang KK; Park JB (Drug Design, Development and Therapy, 2016)
Mi-Seung Shin,1 Dae Ryong Kang,2 Changsoo Kim,3 Eun Joo Cho,4 Ki-Chul Sung,5 Seok-Min Kang,6 Dong-Soo Kim,7 Seung Jae Joo,8 Seung Hwan Lee,9 Kyung-Kuk Hwang,10 Jeong Bae Park11 1Division of Cardiology, Department of Internal Medicine, Gachon University Gil Medical Center, Incheon, 2Office of Biostatistics, Ajou University School of Medicine, Suwon, 3Department of Preventive Medicine, Yonsei University College of Medicine, 4Division of Cardiology, Department of Internal Medicine, St Paul’s Hospital, Catholic University of Korea, 5Division of Cardiology, Department of Internal Medicine, Kangbuk Samsung Hospital, Sungkyunkwan University School of Medicine, 6Cardiology Division, Severance Cardiovascular Hospital and Cardiovascular Research Institute, Yonsei University College of Medicine, Seoul, 7Division of Cardiology, Paik Hospital, Inje University College of Medicine, Busan, 8Division of Cardiology, Jeju National University Hospital, Jeju, 9Division of Cardiology, Wonju Severance Christian Hospital, Wonju Medical College, Yonsei University, Wonju, 10Department of Internal Medicine, Chungbuk National University College of Medicine, Cheongju, 11Division of Medicine/Cardiology, Department of Internal Medicine, Cheil General Hospital, Dankook University College of Medicine, Seoul, South Korea Background: The angiotensin receptor antagonist fimasartan lowered blood pressure (BP) in a previous large population study. The purpose of this study was to evaluate whether fimasartan treatment for 3 months affects clinical and home BP variability in addition to reducing BP.Methods: The study enrolled 1,396 patients (mean age 56.2±10.0 years; males 53.6%) with mild-to-moderate hypertension who had a complete set of home BP measurements (morning and evening) and metabolic risk evaluation. During the 3 months of study, fimasartan alone was used to control BP at a daily dose of 30–120 mg. Clinical and home BP measurements were performed before and after the 3-month treatment. BP variability included beat-to-beat variability (clinical) and day-to-day variability (home).Results: Fimasartan reduced BP after 3 months of treatment. The average reduction of clinical systolic BP (c-SBP) was 15.08±18.36 mmHg (P<0.0001), and the average reduction of morning home SBP (m-SBP) was 11.49±19.33 mmHg (P<0.0001). Beat-to-beat variability as standard deviation (SD) of c-SBP was reduced from 4.56±3.22 to 4.24±3.11 mmHg (P=0.0026). Day-to-day variability as SD of m-SBP was reduced from 7.92±6.74 to 6.95±4.97 mmHg (P<0.0001). Multiple regression analysis revealed an independent association between the change in the SD of c-SBP and the change in c-SBP (P=0.0268) and, similarly, between the change in the SD of m-SBP and the change in m-SBP (P=0.0258), after adjusting for age, sex, body mass index, and change in mean BP.Conclusion: This study indicated that 3 months of fimasartan treatment reduced day-to-day BP variability independent of BP reduction in patients with hypertension. Keywords: angiotensin receptor blockers, hypertension, blood pressure variability